1980
DOI: 10.1172/jci109940
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity to collagen in adjuvant arthritis of rats.

Abstract: A B S T R A C T Arthritis can be induced in rats bv intradermal injection of oil containing bacterial derivatives (adjuvant-induced arthritis) or cartilage collagen (type II collagen-induced arthritis). It was of interest, therefore, to determine whether collagen functions as an autoantigen in rats with adjuvant arthritis. Blood mononuclear cells from the majority of rats with adjuvant arthritis exhibited enhanced thymidine incorporation to homologous types I and II collagens, as well as to purified protein de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…That adjuvant-induced arthritis may be identical to collagen-induced arthritis has been addressed by others (10,11,20). The 2 types of arthritis are phenotypically alike with similar strain distributions of susceptibility (20).…”
Section: Discussionmentioning
confidence: 99%
“…That adjuvant-induced arthritis may be identical to collagen-induced arthritis has been addressed by others (10,11,20). The 2 types of arthritis are phenotypically alike with similar strain distributions of susceptibility (20).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the finding of antibody or T lymphocyte responses to collagen type II in rats with AA (7) and in humans with rheumatoid arthritis (8), it has been suggested that collagen type II may be a critical self-antigen in autoimmune arthritis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Arthritis can be induced in susceptible strains of mice, rats, or nonhuman primates by immunization with heterologous native Type II collagen (CII) (2,3,18), mycobacteria-containing adjuvant [complete Freund's adjuvant CFA)] (14,17), or mycobacterial cell wall fragments suspended in mineral oil (14). These disease models share certain features with human RA, including clinical appearance of the arthritis, aspects of the histopathology including development of a proliferative synovitis, and MHC-linked genetic susceptibility (2,3,14,17,18). However, a detailed histological characterization of disease progression over time in these models has not been reported.…”
Section: Introductionmentioning
confidence: 99%